PENTINGNYA MENANAMKAN PENDIDIKAN KARAKTER UNTUK USIA DINI DI ERA DIGITAL - Anjarwati, Rizqina; Kumalasari, Nina; Asy'ari, Abdurrahman; Dwi Lukitoaji, Beny (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
Early infancy is being exposed to more complicated moral and social issues in the digital age, which is characterized by rapid technological innovation. Character education is essential as the cornerstone for developing well-rounded people at a young age. This study emphasizes how critical it is to incorporate character education into early childhood curricula in order to raise morally upright, resilient, and responsible kids in the face of digital pressures. Digital content consumption without supervision can erode empathy, promote immediate pleasure, and reduce social awareness. As a result, a character education strategy that can adapt to contemporary difficulties is crucial, incorporating virtues like integrity, accountability, tolerance, and responsible use of digital media. In order to create an atmosphere that fosters the development of children's positive character qualities from an early age, this review suggests collaboration between families, schools, and communities.